Responsible Innovation 3 2017
DOI: 10.1007/978-3-319-64834-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ethical Decision Making in Responsible Innovation: The Case of Innovations for Healthy Food

Abstract: In order to strengthen RI in the private sector, it is imperative to understand how companies organise this process, where it takes place (throughout the entire company or on specific levels), and what considerations and motivations are central in the innovation process. In this chapter, the questions of whether and where normative considerations play a role in the innovation process, and whether dimensions of RI are present in the innovation process, are addressed. In order answer these research questions, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…On the other hand, we have observed that only firms with clear moral motives will integrate these label criteria in their innovation policies. These innovation policies will then support the uptake of moral objectives during the product development process [61,80]. Firms with primarily instrumental motives will see the label criteria as a translation of the consumer demand for 'health' and will only use them if this consumer demand provides increased sales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we have observed that only firms with clear moral motives will integrate these label criteria in their innovation policies. These innovation policies will then support the uptake of moral objectives during the product development process [61,80]. Firms with primarily instrumental motives will see the label criteria as a translation of the consumer demand for 'health' and will only use them if this consumer demand provides increased sales.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on RRI in business have indicated that instrumental motives are far more prevalent when the innovation is implemented in a commercial setting [60][61][62][63][64][65]. Furthermore, the study of Pandza & Ellwood [66] shows that, even in academic settings, instrumental motives, such as strategic differentiation, can be one of the main drivers of more inclusive innovation processes [66].…”
Section: Csr Motives and Innovation Practicesmentioning
confidence: 99%
“…Proponents, by contrast, regard R(R)I as full of potential 'to provide an effective conduit for criticisms and the input of critical thinking and reflexivity into science and innovation' ( [16], p. 64; see also [1]). Along these lines, some contributors to the proceedings on the Dutch RI conference series have referred to R(R)I as partly a 'critical analysis' ( [17], p. 89; [18], p. 71) and 'critical reflection' ( [19], p. 357) on scientific practices, assumptions, and knowledge [20,21]. What these different takes on the relation between R(R)I and critique have in common is that they are prevalent in R(R)I discourses, but do not specify critique.…”
Section: Introductionmentioning
confidence: 99%
“…Producers are engaging in product innovations that lead to healthier and less unhealthy products (e.g. light products, vitamin-enriched biscuits), supermarkets are experimenting with pro-health nudging and healthy check-outs, while larger food multinationals are cooperating with governments and NGOs in public-private partnerships to support public health (like co-sponsoring sports events and educating people about healthy food) (Blok, Tempels, Pietersma, & Janssen, 2017;Hartmann, 2011;Knai et al, 2015). So, in terms of product development, marketing and scientific and political involvement, these very same firms are also engaging behaviour that could counter the global obesity epidemic and mitigate food-related NCDs.…”
Section: Involvement In Science and Politicsmentioning
confidence: 99%
“…A front-of-package logo informs consumers and can help them make healthier food choices; for example, the UK traffic light label employs red, amber, and green color coding to indicate the extent to which a product is healthy. Other programs, such as the Dutch Choices Program, do the same while also creating incentives for food companies to innovate and make their products healthier (Blok et al, 2017;Food Standards Agency, 2007;Vyth et al, 2010).…”
Section: A Split Corporate Personalitymentioning
confidence: 99%